Penerapan Algoritma Boyer Moore Pada Aplikasi Kumpulan Cerita Motivasi - Syahri Ramadhani Siregar (Bulletin of Multi-Disciplinary Science and Applied Technology, 2021)
Human behavior is a collection of behaviors that are owned by humans and influenced by customs, attitudes, emotions, values, ethics, power, persuasion or genetics. Human behavior is inseparable from behavior in society which is often referred to as social behavior, social behavior that is specifically addressed to others to give or receive that is related to each other systematically, this behavior is one of the fundamental human needs where humans cannot living alone. According to Max Waber, behavior affects social action in society which then causes problems. To carry out the title search process on the motivational story collection application, the Boyer Moore method is needed. With this method, it can make it easier to find the desired title in the application of a collection of motivational stories.Motivational Story